Dualism in the Supervisory Function of State Institutions: Juridical Analysis of the Authority of the Fertilizer and Pesticide Development Commission to Supervise Distribution Subsidized Fertilizer for Farmers - Ilmiati; Marjana Fahri; Afia Viorita M.; Virna Regita; Syawaluddin Hanafi (Jurisprudentie: Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2023)
This research describes the fertilizer problem in Indonesia and the existence of the Fertilizer and Pesticide Monitoring Commission, this institution was formed which in reality does not solve problems in the agricultural sector. This research is legal research that analyzes the authority of the Fertilizer and Pesticide Monitoring Commission from the perspective of State Administrative Law with a conceptual and statutory approach. The results of this research are: first, the ideal function of KP3 is preventive and repressive supervision. secondly, the supervision carried out by KP3 is only preventive supervision, and even then in the executive area there is overlap between state government organizations.